Fear of self, doubt and obsessive compulsive symptoms. (December 2015) - Nikodijevic, Alexandra; Moulding, Richard; Anglim, Jeromy; Aardema, Frederick; Nedeljkovic, Maja
Abstract: Background and objectives: Following observations in the literature that obsessions often contain or imply negative evaluative information about the self, Aardema et al. (2013) recently developed a measure of feared-self relevant to OCD. The current study aimed to provide further examination of the relevance of such feared self-beliefs to obsessive compulsive processes – in particular whether they partially underlie doubt in OCD-relevant situations. Method: Nonclinical participants (N = 463; 291 females; M age = 25.17, SD = 7.47), were presented with three vignettes, related to washing, checking and non-OCD relevant themes, which assessed doubt through providing alternating sensory and possibility-based information. Results: Higher levels of OCD symptoms and feared-self beliefs both significantly predicted both higher baseline levels of doubt and greater fluctuation in levels of doubt in both the contamination and checking scenarios, and to a much lesser extent in the control scenario. Feared-self beliefs did not predict fluctuation in doubt over-and-above OCD symptoms, consistent with a mediation model. Limitations: The main limitation was the use of a non-clinical sample, although this allowed sufficient participant numbers to test hypotheses. Conclusions: The findings provided further experimental support for reasoning processes in OCD, and suggested that feared self-beliefs may make individuals vulnerable to experiencing doubt. Additionally, these results suggested that individuals with high OCD symptoms and those with high feared self-beliefs are unable to recognise the improbable nature of possibility-based statements. Implications for treatment and theory are discussed. Highlights: Participants given vignettes with alternating doubt/reality-based statements. Individuals high in OCD symptoms more susceptible to possibility-based information. Feared self also led to greater influence of doubt-based information. Results support reasoning-based model of OCD. Feared self belief may partially underlie susceptibility to doubt in OCD.